Potato Suberin Induces Differentiation and Secondary Metabolism in the Genus Streptomyces - Lerat, Sylvain (Japanese Society of Microbial Ecology/The Japanese Society of Soil Microbiology, 2012)
Bacteria of the genus Streptomyces are soil microorganisms with a saprophytic life cycle. Previous studies have revealed that the phytopathogenic agent S. scabiei undergoes metabolic and morphological modifications in the presence of suberin, a complex plant polymer. This paper investigates morphological changes induced by the presence of potato suberin in five species of the genus Streptomyces, with emphasis on S. scabiei. Streptomyces scabiei, S. acidiscabies, S. avermitilis, S. coelicolor and S. melanosporofaciens were grown both in the presence and absence of suberin. In all species tested, the presence of the plant polymer induced the production of aerial hyphae and enhanced resistance to mechanical lysis. The presence of suberin in liquid minimal medium also induced the synthesis of typical secondary metabolites in S. scabiei and S. acidiscabies (thaxtomin A), S. coelicolor (actinorhodin) and S. melanosporofaciens (geldanamycin). In S. scabiei, the presence of suberin modified the fatty acid composition of the bacterial membrane, which translated into higher membrane fluidity. Moreover, suberin also induced thickening of the bacterial cell wall. The present data indicate that suberin hastens cellular differentiation and triggers the onset of secondary metabolism in the genus Streptomyces.